IPTEKS BALANCE SCORECARD DI DINAS KOMUNIKASI INFORMATIKA PERSANDIAN DAN STATISTIK PROVINSI SULAWESI UTARA - Suenaung, Evilyn Mega Anjali; Warongan, Jessy D. L. (Universitas Sam Ratulangi, 2018)
Performance is the achievement or level of success of a person or group of people who have exceeded the standard set. The higher the achievement of the work the better it will be and vice versa. To find out the achievement, it is necessary to measure performance. In the scope of the public sector where performance measurement is very important because performance measurement can help to determine the level of achievement of the success of activities or work program from an agency both within the scope of the region to the center. For the reason, in knowing the level of performance it is necessary to measure performance. Performance measurement in this study uses a balanced scorecard concept, where the performance measurement is assessed based on four perspectives. Where from these four perspectives will be seen the performance achieved by the Office of Communication, Information, Coding and Statistics of North Sulawesi Province. Through the four perspectives of the balance scorecard it will be known in any scope the performance of the Regional Office of Communication, Information, Coding and Statistics of North Sulawesi Province still needs to be emproved.Keywords : Performance, Performance Measurement, Balance Scorecard